2016
DOI: 10.1017/s0017089516000124
|View full text |Cite
|
Sign up to set email alerts
|

A Topological Variation of the Reconstruction Conjecture

Abstract: This paper investigates topological reconstruction, related to the reconstruction conjecture in graph theory. We ask whether the homeomorphism types of subspaces of a space X which are obtained by deleting singletons determine X uniquely up to homeomorphism. If the question can be answered affirmatively, such a space is called reconstructible.We prove that in various cases topological properties can be reconstructed. As main result we find that familiar spaces such as the reals R, the rationals Q and the irrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Most importantly, we see that local properties, so topological properties like local compactness or local connectedness, are reconstructible in T 1 spaces, and further, that for compact Hausdorff spaces, reconstructing compactness is equivalent to reconstructing the space itself. Additional information on the topological reconstruction problem can be found in [17].…”
Section: Topologically Reconstructible Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, we see that local properties, so topological properties like local compactness or local connectedness, are reconstructible in T 1 spaces, and further, that for compact Hausdorff spaces, reconstructing compactness is equivalent to reconstructing the space itself. Additional information on the topological reconstruction problem can be found in [17].…”
Section: Topologically Reconstructible Propertiesmentioning
confidence: 99%
“…For the sphere, stereographic projection gives D(S n ) = {R n }. The second two authors have shown, [17], that all these spaces are reconstructible, as are the rationals, which has deck D(Q) = {Q}, and the irrationals, P , with deck D(P ) = {P }.…”
Section: Introductionmentioning
confidence: 99%
“…The present paper is concerned with the topological version of the reconstruction conjecture, introduced in [21]. A topological space Y is called a card of another space X if Y is homeomorphic to X \ {x} for some x in X.…”
Section: The Topological Reconstruction Problemmentioning
confidence: 99%
“…It is shown in [21] that all the aforementioned examples are reconstructible, with the exception of the Cantor set where we have D(C) = D(C \ {0}). This example also shows that compactness is a non-reconstructible property.…”
Section: The Topological Reconstruction Problemmentioning
confidence: 99%
See 1 more Smart Citation